Errors on Sentence Structures Made by Students in Writing 2 and Writing 4 Classes - Manuela Octaviani; Henny Putri Saking Wijaya (Institute of Research and Community Outreach - Petra Christian University, 2024)
This study analyzed the types of errors on sentence structures by students in Writing 2 and Writing 4 classes in the English Department, Petra Christian University, and their similarities and differences. Eight categories of common errors on sentence structures proposed by Ho (2005) were used to analyze thedrafts. The types of common errors in this study were limited to four: Run-on Sentence, Fragmented Sentence, Inappropriate Subordinate Conjunction, and Misordering. The findings showed that both classes made all types of the errors and the most common error made was run-on sentences in the form of comma splice. Fragmented sentences with missing verb and subject were only found on writing 2 drafts while subordinating clauses in fragmented sentences were found on writing 4 drafts. Moreover, errors in relation to subordinating conjunction were more prominent in Writing 4. In conclusion, difficulties in utilizing conjunctions, and the different complexity of the drafts might affect the errors on sentence structures.